Pola perilaku jemaat terkait ruang interpersonal pada masa Pandemi Covid-19 di Masjid Agung Al-Ukhuwwah-Bandung, Jawa Barat - William Kevin; Indri Astrina Fitria Indrarani Wirakusumah; Aldyfra Luhulima Lukman; Sahid (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
During the pandemic in early 2022, some Muslim congregants chose to close ranks while others kept their distance during prayers and non-ritual activities. Therefore, the aim of this research is to determine the behavior patterns of congregants during the COVID-19 pandemic, specifically at the Great Mosque of Al-Ukhuwwah-Bandung in West Java. The method used involves (1) mapping techniques to observe the congregants' behavior, (2) distributing questionnaires to validate their comfort level with interpersonal space and adherence to health protocols, (3) analyzing the questionnaire results, and (4) drawing conclusions based on the observed behavior patterns and questionnaire analysis results. The research shows that during the Omicron period, the congregants tended to revert to their pre-pandemic behavior patterns, with intimate and personal distance being dominant during ritual and non-ritual activities, respectively. However, the questionnaire results suggest that congregants still adhere to social distancing protocols during activities in the mosque, despite implementing health protocols.